Development Strategy for the Implementation of Entertainment and Recreational Activities at Tourism Objects in Toba Regency - Jerry Wilson (Tourism, Hospitality And Culture Insights Journal, 2021)
The implementation of entertainment and recreation at tourist objects really needs to be considered by tourism actors and local governments. This is very necessary so that tourist guests who come to visit can stay longer and the number of tourists visiting also increases. Because in principle the basic concept in carrying out tourism activities must fulfill three important things, among others, the first is what to see, namely what can be seen. The second is what to do, namely what activities can be done. The third is what to buy, ie anything interesting can be bought. The implementation of entertainment and recreational activities has summarized these three things, namely what to do, what to see and what to buy. Toba Regency also provides entertainment and recreational activities at existing tourist objects but relatively limited availability, facilities and infrastructure. After conducting surveys and discussions with tourists and tourism actors, the implementation of entertainment and recreation facilities still needs to be improved. Because what tourists are interested in is not yet available in several tourist objects on the beach such as volleyball, water bikes, banana boats, entertainment facilities for music and karaoke performances, as well as other entertaining game facilities. Cleanliness, parking lots and barriers for security on the beach still need attention. This causes the number of tourists visiting Toba Regency to decrease in number. In addition to the covid 19 pandemic situation. Entertainment facilities outside of tourist objects that can also be provided are art and cultural performance facilities, sports facilities and activities, culinary bazaars and entertainment activities. others need to be held to attract visiting tourists. The government's role in the strategy for developing the implementation of entertainment and recreation has carried out promotional activities, marketing through existing tourist objects in Toba Regency, but entertainment and recreation facilities have not been optimally arranged in collaboration with existing tourism object actors. Supervision of the implementation of entertainment needs to be maximized so that the facilities and infrastructure available for the implementation of entertainment and recreational activities can be carried out properly, so that tourists can enjoy entertainment and recreational activities and can stay longer in Toba district. Where is currently the average length of visit by tourists is 2 to 4 days. The number of tourists that tends to decrease is added to the current pandemic situation. It can be seen from the statistics on the number of tourists visiting starting from 2016 that domestic tourists who visited were 436,260 people and 11,975 foreign tourists. In 2017, there were 729,445 domestic tourists visiting and 12,121 foreign tourists. In 2018, there were 644,261 domestic tourists visiting and 1242 foreign tourists. In 2019, there were 801,066 domestic tourists visiting and 1611 foreign tourists. In 2020, there were 217,462 domestic tourists visiting and 261 foreign tourists. After analyzing the number of tourists from 2016 to 2019, there was an increase in the number of domestic tourist visits by 54 percent. However, in 2020 the number of domestic tourists decreased drastically to 217,462, there was a drastic decrease of 583,604 people from the latest data in 2019 of 801,066 people or 72 percent. Likewise, foreign tourists experienced a significant decrease from 2017 as many as 12,121 down to 1242 in 2018 and slightly increased in 2019 as many as 1611 people and in 2020 it fell to 261. In 2020 the decline in the number of tourists was indeed caused by the covid 19 pandemic. However, The decline in the number of tourists from 2018 to 2019 still needs further study. The Toba district government has done a lot of development for the advancement of tourism in tourism objects such as promotion and marketing. However, supervision of the implementation of these attractions is still very much needed. Then the Toba Regency government should be able to cooperate with tourism object managers so that the facilities and implementation of entertainment and recreational activities can be well organized and carried out properly in order to increase the number of tourists and tourist satisfaction in visiting entertainment places. and recreation in Toba Regency. The Toba Regency Government should be able to conduct a direct survey of how tourists want to organize entertainment and recreation so that visiting tourists can fulfill their desires to vacation in tourist attractions in Toba Regency. This can increase tourist visits in the years to come. And the toba district government still needs other strategies to increase the success of entertainment and recreation. The analytical method that the author applies is descriptive analysis method to identify the problems that exist in the object of research so that the authors can conclude the problems and identify solutions to the problems in the research.